Discrete element modeling and experimental study of biomechanical properties of cotton stalks in machine-harvested film-stalk mixtures - Jia Zhang; Jianhua Xie; Yakun Du; Yuanze Li; Yong Yue; Silin Cao (Scientific Reports)
Abstract To address the current problems of low accuracy and poor reliability of the discrete element model of cotton stalks, as well as the difficulty of guiding the design and optimization of the equipment through simulations, the discrete element modeling and physical-mechanical tests of cotton stalks in machine harvested film-stalk mixtures are carried out. The peak tensile force $$F_{\rm j}^{\max }$$ F j max , the peak pressure $$F_{\rm y}^{\max }$$ F y max , the peak bending force $$F_{\rm w}^{\max }$$ F w max , the peak shear force $$F_{\rm j}^{\max }$$ F j max , and the force-displacement (F–x) curves of cotton stalks are obtained from the physical tests. The discrete element model of double-layer cotton stalks based on the flat-joint model is established with the PFC $$^{\rm 3D}$$ 3 D software. The $$F_{\rm y}^{\max }$$ F y max is taken as the response value, and the microscopic parameters of the cotton stalk model are used as the test factors, then the Plackett–Burman test, the steepest climb test, and the Box–Behnken test are sequentially designed using Design-Expert software. The second-order regression model describing the relationship between the $$F_{\rm y}^{\max }$$ F y max and the microscopic parameters is established. The optimal parameter combinations of the microscopic parameters are obtained, and then they are utilized to construct the compression, bending, and shear models of cotton stalks and to carry out the validation tests. The results confirm that the established discrete element model could accurately characterize the biomechanical properties of cotton stalks and that the parameter calibration method is reasonable, which could provide a reference for the discrete element modeling of cotton stalks and other stalks, and also offer a theoretical basis for the research of the crushing and separation mechanism of the film-stalk mixtures and the development of the equipment.